Mineral supplement with pre- and probiotic improves respiratory immune status in yearling racing Thoroughbred horses: preliminary results - Michelotto Júnior,Pedro Vicente (2018)
ABSTRACT: There are evidences of intestinal flora influence on the airway immune response. However, this information is scarce with regard to horses. The present preliminary study aimed to investigate the effects of a commercial mineral supplement containing probiotics and prebiotics on the respiratory immune response of horses supplemented with them during the first months of stabling and race training. Twelve TB yearlings were examined at the breeding farm at the beginning of the study (June 2016, henceforth M0) and then reexamined one (July 2016, henceforth M1) and five (November 2016, henceforth M2) months after being stabled at a racetrack in Curitiba, Brazil. Clinical and hematological examinations, airway endoscopy, and tracheal wash (TW) cytology were performed. After the initial examination, horses were randomly divided between the treatment group (TG), which received 10 grams of the supplement daily, and the control group (CG). There was no difference between the groups in terms of clinical parameters; in the hematological examination, eosinophil count was lower in the TG in M1 as compared with M0 (P = 0.045). Pharyngeal lymphoid hyperplasia (PLH) improved in the TG during M1 as compared with M0 (P = 0.007). However, on the CG, PLH remained unchanged. Relative number of eosinophils in the TW was 86.1% higher in M1 than M0 for the CG; in the TG; however, eosinophils were absent and remained within normal limits until M2. In conclusion, this study revealed a positive influence of probiotic and prebiotic supplementation on the respiratory immune response of young TB race horses. Further investigations are recommended.